Hot flushes and quality of life during menopause - Luoto Riitta (BMC, 2009)
Abstract Menopausal health is important since this stage of life is not to be avoided. A recent article in BMC Women's Health from the Estonian Postmenopausal Hormone Therapy trial has concluded that quality of life is not related to hormonal therapy use. The commentary article discusses this finding and considers other factors related to symptoms and quality of life during menopause. Important factors known to affect hot flushes and quality of life are smoking and high body weight. Since both these factors are modifiable, menopause is a suitable area for health promotion. However, evidence concerning lifestyle changes in symptom relief or increase of quality of life is weak. More trials in this area are needed before women may consider non-pharmacological treatment of symptoms as a reliable option for menopausal symptom cure.